PERANCANGAN ANIMASI 3 DIMENSI ISLAM DENGAN MENERAPKAN METODE POSE TO POSE “DUO DURO : SABAR” - Raditya, Rifqi Azhar; Agustin, Nanda Bintang; Roynaldi, Kholid; Aziz, Sulthon Abdul; Munawaroh, Siti; Zahrah, Yusminnu (Anima Rupa, 2025)
The integration of digital technology in education is crucial to prepare the younger generation for Industry 4.0, emphasizing on technological skills and moral values. However, challenges such as inadequate IT skills among educators and inadequate infrastructure hinder the effective use of technology in learning. This research advocates the use of multimedia, particularly 3D animation, to enhance student engagement and their understanding of complex concepts. Blender, an open-source 3D authoring tool, is highlighted for its flexibility and cost-effectiveness in producing high-quality animations. This article presents a case study of an Islamic-themed animation, "Don't Be Too Quick to Judge," created using the pose-to-pose animation method. This approach ensures clarity and consistency in conveying the moral message. The animation production process is described in three stages: pre-production (ideation, scriptwriting, storyboarding), production (modeling, texturing, lighting, rigging, animation, rendering), and post-production (compositing, color correction, final output). This comprehensive workflow aims to show how 3D animation can be an effective educational tool.